Profil Pelajar Pancasila: Internalisasinya Dalam Ekstrakurikuler Hizbul Wathan Di SMP Muhammadiyah 08 Batu - Wibowo, Arif Prasetyo; Mansur, M; Ayudini, Ivanatasha Juwita (Jurnal Civic Hukum, 2024)
This research aims to (01) Find out the Profile of Pancasila Students at Junior High School 08 Batu, (02) Find out further analysis of the application or internalization of elements regarding the ancasila Student Profile in Hizbul Wathan activities at Junior High School 08 Batu, (03) Foind out the inhibiting factors and suporting factors in the process of internalizing the elements of strengthening the Pancasila Student profile in Hizbul Wathan activities at Junior High Schol Muhamamadiyah 08 Batu, (04) Knowing the solutions that can be implemented in dealing with the inhibiting factors that occur in the process of internalising the elements of strengthening the Creative Pancasila Student Profile in Hizbul Wathan at Junior High School Muhammadiyah 08 Batu rock. This research uses a qualitative approach with descriptive methods, with the aim of finding out and describing how the process of internalizing the elements of strengthening the Creative Pancasila Student Profile is implemented at Junior High School 08 Batu. Data Collection techniques through observation, interviews and documentation, and data validity techniques using data triangulation techniques. The result obtained from this research are that Junior High School 08 Batu is one of the driving schools for the Strengthening Pancasila Student Profile program which is implemented in the realm of intracurricular, extracurricular, school culture, and projects. The internalization of the Creative Pancasila Profile Elements in the Hizbul Wathan Extracurricular at Junior High School 08 Batu was instilled through several scouting activity programs such as pioneering, marching, rigging, and the creation of chants with the results of their implementation being carried out well.